The Oncogenic Potential of the Pax3-FKHR Fusion Protein Requires the Pax3 Homeodomain Recognition Helix but Not the Pax3 Paired-Box DNA Binding Domain - Lam, Paula Y. P. (American Society for Microbiology, 1999)
The chimeric transcription factor Pax3-FKHR, produced by the t(2;13)(q35;q14) chromosomal translocation in alveolar rhabdomyosarcoma, consists of the two Pax3 DNA binding domains (paired box and homeodomain) fused to the C-terminal forkhead (FKHR) sequences that contain a potent transcriptional activation domain. To determine which of these domains are required for cellular transformation, Pax3, Pax3-FKHR, and selected mutants were retrovirally expressed in NIH 3T3 cells and evaluated for their capacity to promote anchorage-independent cell growth. Mutational analysis revealed that both the third α-helix of the homeodomain and a small region of the FKHR transactivation domain are absolutely required for efficient transformation by the Pax3-FKHR fusion protein. Surprisingly, point mutations in the paired domain that abrogate sequence-specific DNA binding retained transformation potential equivalent to that of the wild-type protein. This finding suggests that DNA binding mediated through the Pax3 paired box is not required for transformation. Our results demonstrate that the integrity of the Pax3 homeodomain recognition helix and the FKHR transactivation domain is necessary for efficient cellular transformation by the Pax3-FKHR fusion protein.